Ways of modernization of visual situation of aviation training apparatus - Пеньков, А. А.; Полетаев, Н. С.; Шевченко, Р. А. (Proceedings of National Aviation University (archive), 1999)
Considered is possibility of prolongation of "life-cycle" of visual situation simulator of aviation training apparatus and the ways of improving the quality of image modeling